Chemically strengthened glass-ceramics and its manufacturing method

By heat treatment of the crystalline glass to form a crystalless surface region, the problems of degraded chemical strengthening performance and excessive surface stress of the crystalline glass are solved, and better chemical strengthening performance and edge stability are achieved.

JP7657403B2Active Publication Date: 2025-04-07AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022540305
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-31
Filing Date
2021-07-26
Publication Date
2025-04-07
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

After chemical reinforcement treatment, the chemical reinforcement performance of crystallized glass decreases, and excessive surface stress can easily lead to edge damage.

Method used

After crystallization of the crystalline glass, heat treatment is performed in a reduced pressure atmosphere to form a crystalline region with shallow surface layer, which improves the chemical strengthening performance after chemical strengthening treatment and reduces surface stress.

Benefits of technology

It improves the chemical reinforcement properties of crystalline glass, reduces surface stress, and prevents damage to the rear edge of chemical reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657403000003
    Figure 0007657403000003
  • Figure 0007657403000004
    Figure 0007657403000004
  • Figure 0007657403000005
    Figure 0007657403000005
Patent Text Reader

Abstract

The present invention pertains to a chemically strengthened crystallized glass containing a crystalline phase having two main surfaces facing each other, wherein an amorphization region is formed on the surface layer of at least one of the main surfaces, a crystallization region is formed inside the glass, and the crystallinity at a depth of 100 nm from the outermost layer on which the amorphization region is formed is 10 vol% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemically strengthened crystallized glass containing a crystalline phase and a method for producing the same. [Background technology]

[0002] In electronic devices such as mobile phones and smartphones, thin and strong chemically strengthened glass is used as a cover glass to protect the display. As a glass base material to be subjected to chemical strengthening treatment, crystallized glass has attracted attention for the purpose of further improving strength.

[0003] Glass-ceramics are made by subjecting amorphous glass to heat treatment to precipitate a high-strength crystalline phase in the glass, and can obtain higher strength than amorphous glass that does not contain a crystalline phase. Therefore, it is considered that by subjecting glass-ceramics to chemical strengthening treatment to obtain chemically strengthened glass-ceramics, glass with even higher strength than conventional chemically strengthened glass can be obtained. For example, Patent Document 1 describes an example of chemically strengthening glass-ceramics, which is glass-ceramics. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japan Special Publication No. 2016-529201 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the chemical strengthening properties of crystallized glass tend to deteriorate. This is because crystallized glass has both a glass phase and a crystalline phase, and ion exchange is less likely to occur in the crystalline phase than in the glass phase. In addition, the compressive stress value of the surface of crystallized glass tends to be high after chemical strengthening treatment, and if this value is too high, the edge may chip after chemical strengthening treatment. This phenomenon is called chipping.

[0006] In view of the above, an object of the present invention is to provide chemically strengthened crystallized glass having excellent chemical strengthening properties and reduced surface stress, and a method for producing the same. [Means for solving the problem]

[0007] As a result of intensive research, the inventors have found that by performing a heat treatment in a reducing atmosphere after performing a crystallization treatment on amorphous glass, the degree of crystallization near the main surface of the obtained crystallized glass can be reduced and an amorphous region can be formed. This activates the ion exchange with the molten salt that occurs on the glass surface during chemical strengthening treatment, and increases the concentration difference between the amorphous region near the main surface and the inside of the crystallized glass. As a result, the ion diffusion rate toward the inside of the glass is improved, and the chemical strengthening properties of the entire crystallized glass are improved.

[0008] On the other hand, by forming an amorphous region near the main surface of the crystallized glass, the glass transition temperature Tg of the surface layer becomes lower than the glass transition temperature Tg of the inside of the crystallized glass. Therefore, only the compressive stress near the main surface, which does not affect the strength of the crystallized glass as a whole, is relaxed, and chipping of the chemically strengthened crystallized glass after chemical strengthening treatment is suppressed.

[0009] That is, the present invention is as follows. [1] A chemically strengthened crystallized glass containing a crystalline phase, the chemically strengthened crystallized glass having two mutually opposing main surfaces, an amorphous region on the surface layer of at least one of the main surfaces, and a crystallized region inside the glass, the degree of crystallization of the amorphous region at a depth of 100 nm from the outermost surface being 10 volume % or less. [2] Sodium is contained, and the sodium concentration at a depth of 10 nm from the outermost surface is defined as [Na]0 (mol%), and the sodium concentration at a depth of 10 nm from the outermost surface calculated by fitting the sodium concentration profile in a region 10 to 200 μm deep from the outermost surface to the following formula (1) by the least squares method is defined as [Na] c When this is done, |[Na]0-[Na] cThe chemically strengthened glass-ceramics according to the above [1], wherein the absolute value of the sodium concentration difference represented by | is 10 mol % or less. y = A × erfc(x × B) + C (1) (In the formula, y is the sodium concentration (mol%), x is the depth from the main surface (μm), erfc is the complementary error function, A, B, and C are constants, and 0≦x≦200.) [3] The chemically strengthened crystallized glass according to [1] or [2] above, wherein the average crystallinity of the crystallized regions is 20 to 80 volume %. [4] The chemically strengthened crystallized glass according to any one of [1] to [3] above, wherein the depth of the amorphous region is 10 μm or less. [5] The chemically strengthened glass-ceramics according to any one of [1] to [4], wherein the compressive stress value CS0 at the outermost surface is 200 to 900 MPa. [6] The chemically strengthened crystallized glass according to any one of [1] to [5] above, wherein the depth from the outermost surface at which the compressive stress value CS is maximum is 0.1 to 10 μm. [7] The chemically strengthened crystallized glass according to any one of the above [2] to [6], wherein the sodium ion diffusion depth is (t×0.05) to (t×0.2) μm, where t μm is the thickness of the glass. [8] The chemically strengthened crystallized glass according to any one of the above [1] to [7], wherein the crystalline phase contains atoms having a first ionization energy of 8 eV or less. [9] The chemically strengthened glass-ceramics according to any one of [1] to [8] above, containing, in mass % on an oxide basis, 45 to 75% SiO2, 1 to 30% Al2O3, 1 to 25% Li2O, 0 to 15% Na2O, 0 to 8% K2O, 0 to 15% in total of one or more of SnO2 and ZrO2, and 0 to 15% P2O5.

[0010]

[10] Preparing an amorphous glass, subjecting the amorphous glass to a first heat treatment to obtain a crystallized glass containing a crystal phase, subjecting the crystallized glass to a second heat treatment in a reducing atmosphere to obtain a crystallized glass having an amorphous region formed in the surface layer of at least one main surface, and chemically strengthening the crystallized glass having the amorphous region formed therein, in this order, a method for manufacturing a chemically strengthened crystallized glass.

[11] The method for manufacturing a chemically strengthened crystallized glass according to

[10] , wherein the amorphous region is formed in a region having a depth of 10 μm or less from the outermost surface, and the crystallinity at a depth of 100 nm from the outermost surface of the amorphous region is 10% by volume or less.

[12] The method for manufacturing a chemically strengthened crystallized glass according to

[10] or

[11] , wherein the average crystallinity of the crystallized glass obtained by the first heat treatment is 20 to 80% by volume.

[13] The method for manufacturing a chemically strengthened crystallized glass according to any one of

[10] to

[12] , wherein the glass transition temperature Tg of the amorphous glass is 550°C or less.

[14] The method for manufacturing a chemically strengthened crystallized glass according to any one of

[10] to

[13] , wherein the heat treatment temperature T2 (°C) in the second heat treatment satisfies the relationship of (Tg - 200)°C < T2 < (Tg + 200)°C with respect to the glass transition temperature Tg (°C) of the amorphous glass.

[15] The method for manufacturing a chemically strengthened crystallized glass according to any one of

[10] to

[14] , wherein the second heat treatment is performed in a state where carbon is in contact with the crystallized glass.

[16] The method for manufacturing a chemically strengthened crystallized glass according to any one of

[10] to

[15] , wherein the glass is formed into a shape having a curved portion during the second heat treatment.

[17] The method for manufacturing a chemically strengthened crystallized glass according to any one of

[10] to

[16] , wherein the crystal phase contains an atom having an ionization energy of 8 eV or less.

[18] The method for producing chemically strengthened crystallized glass according to any one of

[10] to

[17] above, wherein the amorphous glass contains, in mass % on an oxide basis, 45 to 75% SiO2, 1 to 30% Al2O3, 1 to 25% Li2O, 0 to 15% Na2O, 0 to 8% K2O, 0 to 15% in total of one or more of SnO2 and ZrO2, and 0 to 15% P2O5. Effect of the Invention

[0011] According to the present invention, a chemically strengthened crystallized glass having excellent chemical strengthening properties and reduced surface stress can be obtained. As a result, excellent strength properties can be achieved by the chemical strengthening treatment, while chipping of the edge portion after the chemical strengthening treatment can be suppressed. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a transmission electron microscope (TEM) image of the amorphous glass in Example 3 before being subjected to the first heat treatment. [Diagram 2] FIG. 2 is a TEM image of the crystallized glass obtained after the first heat treatment in Example 3. [Diagram 3] FIG. 3 is a TEM image of the glass-ceramics in which amorphous regions were formed, obtained after the second heat treatment in Example 3. [Figure 4] FIG. 4 is a graph showing the relationship between the degree of crystallinity of the chemically strengthened crystallized glass of Example 2 and the depth from the outermost surface. [Diagram 5] FIG. 5 shows the stress profile of the chemically strengthened glass-ceramics of Example 2. [Figure 6] FIG. 6 is a graph showing the relationship between the degree of crystallinity of the chemically strengthened crystallized glass of Example 3 and the depth from the outermost surface. [Figure 7] FIG. 7 shows the stress profile of the chemically strengthened glass-ceramics of Example 3. [Figure 8] FIG. 8 is a graph showing the relationship between the sodium concentration and the depth from the outermost surface of the chemically strengthened crystallized glass of Example 2. [Figure 9]FIG. 9 is a graph showing the relationship between the sodium concentration and the depth from the outermost surface of the chemically strengthened crystallized glass of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below. In this specification, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0014] In this specification, "amorphous glass" refers to glass that does not show diffraction peaks indicating crystals by powder X-ray diffraction. "Crystallized glass" refers to glass that contains a crystalline phase and is obtained by heating "amorphous glass" to precipitate a crystalline phase. The "crystallinity" of glass refers to the volume fraction of the crystalline phase contained in the glass. In other words, a crystallinity of 0% by volume means that the glass does not contain any crystalline phase and is composed only of the glass phase, i.e., the amorphous phase. The degree of crystallinity is calculated from the TEM image of the glass. Specifically, the total area of ​​the crystalline phase present within a range of 1 μm in the direction parallel to the main surface and 0.05 μm in the depth direction is calculated from the TEM image of the target depth. 2 The proportion of crystalline phases present calculated by X / 0.05 is taken as the degree of crystallinity (volume %).

[0015] In this specification, "chemically strengthened glass-ceramics" refers to glass that has been subjected to chemical strengthening treatment. Except for cases where extreme ion exchange treatment has been performed, the glass composition of the chemically strengthened glass-ceramics deeper than the depth of compressive stress layer (DOL) is the same as the glass composition of the glass-ceramics before chemical strengthening treatment. Therefore, the base composition of the chemically strengthened glass-ceramics and the glass composition of the glass-ceramics before chemical strengthening treatment can be considered to be the same. Furthermore, the glass composition of the amorphous glass used as the raw material and the crystallized glass after the crystal phase has been precipitated by heat treatment may be considered to be the same, and the glass composition of the crystallized glass and the crystallized glass with an amorphous region formed on the surface layer may be considered to be the same. Therefore, the chemically strengthened crystallized glass according to this embodiment and its raw material amorphous glass, crystallized glass, and crystallized glass having an amorphous region may be regarded as having the same glass composition.

[0016] In this specification, unless otherwise specified, the glass composition is expressed in mass% based on oxide, and mass% may be expressed simply as "%". In addition, "substantially free" means that it is below the impurity level contained in raw materials, that is, it is not intentionally added. In this specification, when it is described that a certain component is substantially free, the content of the component is specifically, for example, less than 0.1 mass%.

[0017] In this specification, the term "stress profile" refers to a representation of compressive stress values ​​(CS) with the depth from the outermost surface of the glass as a variable. In the stress profile, tensile stress is represented as negative compressive stress. The compressive stress value at the outermost surface of the glass is represented as CS0. The maximum compressive stress value is represented as CS0. max It is expressed as: In this specification, the "sodium ion diffusion depth" is the depth at which a change in sodium concentration is observed, and when the sodium ion diffusion depth is shallow, it can be regarded as being the same as the compressive stress layer depth (DOL), which means the depth at which the compressive stress value (CS) is zero. Specifically, when the compressive stress layer depth is less than 1 / 5 of the glass thickness, the sodium ion diffusion depth and the compressive stress layer depth can be regarded as being the same. On the other hand, when the compressive stress layer depth is 1 / 5 or more of the glass thickness, the sodium ion diffusion depth and the compressive stress layer depth do not match. When the sodium ion diffusion depth and the compressive stress layer depth do not match, the sodium ion diffusion depth is determined by measurement using an electron probe microanalyzer (EPMA).

[0018] <Chemically strengthened glass-ceramics> The chemically strengthened crystallized glass according to this embodiment (hereinafter, simply referred to as "crystallized glass") has two main surfaces facing each other, and has an amorphous region on the surface layer of at least one of the main surfaces. Also, the glass has a crystallized region inside.

[0019] The degree of crystallinity in the region within the glass where the rate of change in crystallinity is within ±5% is defined as the "average crystallinity (volume%) of the crystallized region." In contrast, a region that shows a crystallinity of equal to or greater than (average crystallinity of the crystallized region - 5% by volume) is a crystallized region, and the average crystallinity of the crystallized region is greater than 15% by volume. The amorphous region is formed in a surface layer on at least one of the main surfaces of the crystallized glass, and is a region having a crystallinity of 10% by volume or less. Between the crystallized region and the amorphous region, there is a transition region. That is, the transition region is a region in which the crystallinity is more than 10% by volume and less than the average crystallinity of the crystallized region minus 5% by volume. However, when the average crystallinity of the crystallized region is just above 15% by volume, the transition region is so narrow that it cannot be recognized, and the crystallized region and the amorphous region may appear to be continuous.

[0020] (amorphous region) The degree of crystallinity of the amorphous region at a depth of 100 nm from the outermost surface of the glass is 10% by volume or less, preferably 8% by volume or less, and more preferably 5% by volume or less. The lower limit of the degree of crystallinity is 0% by volume, i.e., no crystalline phase may be included.

[0021] The presence of a large amount of glass phase, i.e., amorphous phase, in the surface layer of crystallized glass improves the chemical strengthening characteristics. Specifically, the glass phase has a larger concentration difference between the main surface and the inside of the glass during chemical strengthening treatment than the crystalline phase, and the ion diffusion rate toward the inside of the glass improves. Therefore, the compressive stress layer depth also becomes deeper, and the deep layer stress tends to improve. In addition, since the glass transition temperature Tg of the glass phase is lower than that of the crystalline phase, the presence of a large amount of glass phase relieves the compressive stress on the surface, thereby suppressing chipping after chemical strengthening treatment of the crystallized glass.

[0022] Furthermore, if the surface layer of the crystallized glass contains a large amount of crystalline phase, ion exchange in the crystalline phase will proceed during chemical strengthening, and the amount of ion exchange in the remaining glass portion will decrease, which may lead to a decrease in the compressive stress of the remaining glass portion. On the other hand, if the glass phase contains a large amount of glass, the amount of ion exchange in the glass phase will increase during chemical strengthening, which may prevent the above-mentioned decrease in compressive stress of the remaining glass portion. This is because, assuming that the total amount of ions exchanged in the chemical strengthening treatment is constant, the more the amount of ions exchanged in the crystalline phase increases, the less the amount of ions exchanged in the remaining glass portion decreases. In other words, it is presumed that when the amount of ions exchanged in the crystalline phase is large, the amount of ions exchanged in the remaining glass portion decreases, and therefore the stress generated in the remaining glass portion decreases.

[0023] The presence of amorphous regions in crystallized glass reduces surface stress as described above. Usually, when surface stress is reduced, the fracture strength in bending mode is reduced. However, the chemically strengthened crystallized glass according to the present embodiment shows excellent fracture strength. This is presumably because latent scratches exist on the glass surface, and in regions that are very shallow from the outermost surface, the influence of these latent scratches is large, and even if stress is reduced, it does not have a large effect on fracture strength.

[0024] From the viewpoint of suppressing a decrease in fracture strength due to bending mode, it is preferable that the depth of the amorphous region is shallow, and the depth from the outermost surface of the glass is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 5 μm or less, even more preferably 3 μm or less, especially preferably 1 μm or less, particularly preferably 0.5 μm or less, and most preferably 0.3 μm or less. On the other hand, from the viewpoint of improving chemical strengthening properties, the depth of the amorphous region is 0.1 μm or more, and preferably 0.15 μm or more.

[0025] In the chemically strengthened glass-ceramics, for example, Li ions in the glass-ceramics are ion-exchanged with Na ions or K ions, and Na ions in the glass-ceramics are ion-exchanged with K ions by chemical strengthening treatment. Among them, it is preferable that Li ions in the glass-ceramics are ion-exchanged with Na ions, and it is preferable that the glass-ceramics contains sodium.

[0026] The sodium concentration in the amorphous region is calculated by the following two methods: [Na]0 (mol%) and [Na] c It is preferable that the difference (mol %) is small. The sodium concentration [Na]0 at a depth of 10 nm from the outermost surface is a value measured by X-ray photoelectron spectroscopy (XPS). Sodium concentration at a depth of 10 nm from the surface [Na] c is a value calculated by fitting the sodium concentration profile in a region 10 to 200 μm deep from the outermost surface to the following formula (1) by the least squares method. Sodium concentration [Na] c In calculating the sodium concentration at a depth of 10 nm from the outermost surface, i.e., (t×1 / 2) μm, if the glass thickness t is 400 μm or less, the area covered is from 10 μm deep from the outermost surface to half the glass thickness, i.e., (t×1 / 2) μm. The sodium concentration profile in this area is then fitted to the following formula (1) to obtain the sodium concentration [Na] at a depth of 10 nm from the outermost surface. c Calculate. y = A × erfc(x × B) + C (1) (In the formula, y is the sodium concentration (mol%), x is the depth from the main surface (μm), erfc is the complementary error function, A, B, and C are constants, and 0≦x≦200.)

[0027] The above [Na]0 and [Na] c Using |[Na]0-[Na] cThe absolute value of the sodium concentration difference represented by | is preferably 10 mol% or less, more preferably 8 mol% or less, even more preferably 5 mol% or less, even more preferably 2 mol% or less, even more preferably 1.5 mol% or less, and particularly preferably 1 mol% or less. The lower limit is not particularly limited, and is 0, i.e., [Na]0=[Na] c may be also possible.

[0028] Also, [Na]0 is [Na] c For ([Na] c × 0.5) or more is preferable, ([Na] c × 0.7) or more is preferable, ([Na] c × 0.8) or more is more preferable, and ([Na] c × 1.5) or less is preferable, ([Na] c × 1.4) or less is more preferable, ([Na] c × 1.3) or less is more preferable. c × 1.5) or less, the stress in the outermost layer becomes too large, and the compressive stress value CS at a depth of 50 μm, which affects the drop strength, 50 It is possible to suppress a decrease in the

[0029] (crystallization region) The crystallized region is a region exhibiting a crystallinity of (the average crystallinity of the crystallized region - 5% by volume) or more. The average crystallinity of the crystallized region is more than 15% by volume, and from the viewpoint of realizing a more desired stress profile by relaxing the structure due to heat during chemical strengthening treatment, it is preferably 20% by volume or more, more preferably 25% by volume or more, and even more preferably 30% by volume or more. On the other hand, from the viewpoint of maintaining the transparency of the glass, the average crystallinity is preferably 80% by volume or less, more preferably 75% by volume or less, and even more preferably 70% by volume or less.

[0030] (transition area) The transition region is a region between the crystallized and amorphous regions, with a crystallinity of more than 10% by volume and less than the average crystallinity of the crystallized regions minus 5% by volume. The existence of transition region means that the crystallized glass is not formed by bonding another amorphous glass or a crystallized glass with low crystallinity to the surface of the crystallized glass, which becomes an amorphous region. That is, the surface layer of the uniform crystallized glass is heat-treated in, for example, a reducing atmosphere to form an amorphous region derived from the above-mentioned crystallized glass, and the transition region exists between the amorphous region and the crystallized region. That is, the crystallinity does not change discontinuously at the boundary between the amorphous region and the crystallized region, but changes continuously, so that the transition region exists.

[0031] The thickness of the transition region varies depending on the average crystallinity of the crystallized region, the thickness of the amorphous region, etc., but is usually 5 μm or less. Depending on the crystallinity of the crystallized region, the transition region may not exist and the amorphous region and the crystallized region may be adjacent to each other.

[0032] (crystalline phase) In order to form an amorphous region on the surface layer of the crystallized glass, for example, heat treatment is performed in a reducing atmosphere. In this amorphization, the ease of reduction of atoms in the crystal affects the amorphization. The redox state is determined by the ionization energy, but since atoms that are easily reduced are necessary to cause amorphization, it is preferable that the crystal phase contains atoms with a first ionization energy of 6 eV or more. It is more preferable that the crystal phase contains atoms with a first ionization energy of 6.5 eV or more, even more preferable that it contains atoms with a first ionization energy of 7 eV or more, and even more preferable that it contains atoms with a first ionization energy of 7.5 eV or more. The upper limit of the first ionization energy of the easily reduced atoms is not particularly limited, but is usually 14 eV or less.

[0033] On the other hand, in order to prevent excessive reduction from causing coloration, the crystalline phase preferably contains, in addition to the easily reduced atoms, atoms with a first ionization energy of 9 eV or less. More preferably, the crystalline phase simultaneously contains atoms with a first ionization energy of 8 eV or less, even more preferably atoms with a first ionization energy of 7 eV or less, and even more preferably atoms with a first ionization energy of 6.5 eV or less. The lower limit of the first ionization energy of this atom is not particularly limited, but is usually 4 eV or more.

[0034] Specific examples of atoms that are easily reduced and have a first ionization energy of 6 eV or more include Si (8.2 eV), P (10.5 eV), Mg (7.7 eV), etc. Among these, it is preferable to contain Si and P. Specific examples of atoms that suppress excessive reduction and have a first ionization energy of 9 eV or less include Li (5.4 eV), Na (5.2 eV), K (4.4 eV), Al (6.0 eV), etc. Among these, it is preferable to contain Li and Na.

[0035] Examples of crystals constituting the crystal phase containing these atoms include lithium aluminosilicate crystals and lithium silicate crystals. When lithium aluminosilicate crystals or lithium silicate crystals are contained, these crystals are also ion-exchanged by the chemical strengthening treatment, so that high strength can be obtained.

[0036] Examples of lithium aluminosilicate crystals include β-spodumene crystals (LiAlSi2O6) and petalite crystals (LiAlSi4O 10 ) Examples of lithium silicate crystals include lithium metasilicate crystals (Li2SiO3) and lithium disilicate crystals (Li2Si2O5). These crystals can be selected according to the purpose, but for example, when it is desired to increase the strength after chemical strengthening treatment, it is preferable to contain β-spodumene crystals. When it is desired to improve transparency and formability while maintaining chemical strengthening properties, it is preferable to contain lithium metasilicate crystals. When it is desired to lower the bending forming temperature, it is preferable to contain petalite crystals or lithium metasilicate crystals.

[0037] From the viewpoint of maintaining the transparency of the glass, the average particle size of the crystal phase is preferably 300 nm or less, more preferably 200 nm or less, further preferably 150 nm or less, and particularly preferably 100 nm or less. The average particle size of the precipitated crystals can be calculated from the powder X-ray diffraction intensity by the Rietveld method.

[0038] (Physical Properties) In the chemically strengthened crystallized glass according to this embodiment, the Tg of the amorphous region is lower than the Tg of the crystallized region, and therefore the compressive stress value CS0 of the outermost surface tends to be smaller than that of chemically strengthened crystallized glass that does not have an amorphous region. That is, the maximum compressive stress value of the crystallized glass, CS max On the other hand, it is preferable that the compressive stress value CS0 of the outermost surface is low.

[0039] The compressive stress value CS0 of the outermost surface where the amorphous region exists cannot be generally stated because it varies depending on the conditions of the chemical strengthening treatment and the glass composition, etc., but from the viewpoint of obtaining excellent fracture strength as a crystallized glass, it is preferably 200 MPa or more, more preferably 230 MPa or more, and even more preferably 250 MPa or more. On the other hand, when stress relaxation due to the amorphous region is taken into account, the compressive stress is lower than the effect of the chemical strengthening treatment on the crystallized region. Therefore, considering the effect due to the presence of the amorphous region, from the viewpoint of suppressing chipping, the compressive stress value CS0 of the outermost surface is preferably 900 MPa or less, more preferably 850 MPa or less, and even more preferably 800 MPa or less.

[0040] The compressive stress value CS0 of the outermost surface is the maximum compressive stress value CS maxFrom the viewpoint of obtaining excellent fracture strength as a crystallized glass, (CS max × 0.2) MPa or more is preferable, and (CS max ×0.3) MPa or more is more preferable, and (CS max In addition, taking into consideration the effect of the presence of the amorphous region, the compressive stress value CS0 of the outermost surface is preferably (CS max × 0.9) MPa or less is preferable, and (CS max × 0.8) MPa or less is more preferable, and (CS max × 0.7 MPa or less is even more preferable.

[0041] Maximum compressive stress value CS max Considering the presence of an amorphous region, the depth from the outermost surface at which this occurs is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less.

[0042] Maximum compressive stress value CS max Although it cannot be said in general because it varies depending on the conditions of the chemical strengthening treatment and the glass composition, from the viewpoint of preventing cracking due to deformation such as bending, it is preferably 500 MPa or more, more preferably 600 MPa or more, and even more preferably 800 MPa or more. max The upper limit is not particularly limited, but is, for example, 1500 MPa or less.

[0043] The four-point bending strength of crystallized glass is greatly affected by latent scratches on the glass surface. Therefore, the correlation with the four-point bending strength is higher for the compressive stress value at a depth of several μm from the outermost surface than for the compressive stress value CS0 at the outermost surface. As an example of the index, the compressive stress value CS5 at a depth of 5 μm from the outermost surface can be adopted. From the viewpoint of obtaining high bending strength, CS5 is preferably 600 MPa or more, more preferably 650 MPa or more. In addition, the upper limit of CS5 is not particularly limited, but is, for example, 1300 MPa or less.

[0044] The drop strength of crystallized glass can be measured using the compressive stress value at a certain depth from the outermost surface. As an example, the compressive stress value CS at a depth of 50 μm from the outermost surface is 50 Using CS 50 From the viewpoint of obtaining high drop strength, the CS is preferably 110 MPa or more, more preferably 150 MPa or more, and even more preferably 200 MPa or more. 50 The upper limit is not particularly limited, but is, for example, 300 MPa or less.

[0045] It is preferable that the lithium ions in the crystallized glass are exchanged for sodium ions by chemical strengthening treatment. In this case, the sodium ion diffusion depth is preferably (t×0.05) μm or more, more preferably (t×0.08) μm or more, and even more preferably (t×0.1) μm or more, relative to the thickness t μm of the glass, from the viewpoint of preventing the glass surface from breaking when scratched. Also, from the viewpoint of preventing explosive fracture when scratched due to excessive tensile stress, the sodium ion diffusion depth is preferably (t×0.2) μm or less, more preferably (t×0.18) μm or less, and even more preferably (t×0.15) μm or less. When the lithium ions in the crystallized glass are not exchanged for sodium ions, it is preferable that the depth of the compressive stress layer (DOL) satisfies the above range.

[0046] The thickness t of the chemically strengthened crystallized glass is not particularly limited, but from the viewpoint of obtaining the necessary strength as a cover glass, it is preferably 200 μm or more, more preferably 300 μm or more, and even more preferably 400 μm or more. In addition, in consideration of the use form as a cover glass, the thickness is preferably 2 mm or less, more preferably 1.5 mm or less, and even more preferably 1 mm or less.

[0047] The chemically strengthened crystallized glass may be in a flat plate shape or may have a curved shape. A shape having a curved portion means a three-dimensional shape obtained by bending a flat plate. The three-dimensional shape is not limited to a shape having a uniform thickness overall, and may have portions with different thicknesses. As a shape having a curved portion, for example, the central portion of the main surface may be flat and a pair of opposing ends may be concave or convex, or the entire glass may be curved. Also, the shape may be composed of multiple R shapes.

[0048] The four-point bending strength of the chemically strengthened crystallized glass is preferably 500 MPa or more, more preferably 550 MPa or more, and even more preferably 600 MPa or more. The four-point bending strength is measured using a test piece of 40 mm x 5 mm x 0.7 mm under the conditions of a lower span, i.e., a distance between the outer supports of the holder, of 30 mm, an upper span, i.e., a distance between the inner supports, of 10 mm, and a crosshead speed of 0.5 mm / min. This measurement is performed on 10 test pieces, and the average value of the obtained results is taken as the four-point bending strength.

[0049] The drop strength of the chemically strengthened crystallized glass is preferably 100 cm or more, more preferably 120 cm or more, and even more preferably 150 cm or more. The drop strength is measured using a test piece of 120 mm x 60 mm x 0.7 mm, which is likened to the cover glass of a smartphone. Specifically, the test piece is attached to a housing simulating a smartphone and dropped onto a flat surface on which 180-grit sandpaper is placed. At this time, the mass of the test piece and the housing together is about 140 g. The drop test is started from a height of 30 cm, and if the glass plate, which is the test piece, does not break, the test is repeated by increasing the height by 10 cm, and the height at which it breaks is recorded. This test is considered as one set, and 10 sets are repeated, and the average value of the height at which it breaks is the drop strength.

[0050] (Glass composition) The glass composition of the chemically strengthened glass-ceramics preferably contains, in mass % on an oxide basis, 45-75% SiO2, 1-30% Al2O3, 1-25% Li2O, 0-15% Na2O, 0-8% K2O, 0-15% in total of one or more of SnO2 and ZrO2, and 0-15% P2O5. As described above, the chemically strengthened crystallized glass according to this embodiment and its raw materials, amorphous glass, crystallized glass, and crystallized glass having an amorphous region, can all be regarded as having the same glass composition, and the preferred ranges are also the same.

[0051] The preferred embodiment of the above glass composition varies depending on the crystals that constitute the crystal phase. For example, when the crystal phase contains lithium aluminosilicate crystals, it is more preferable that the crystal phase contains, in mass % on an oxide basis, 58 to 74% SiO2, 5 to 30% Al2O3, 1 to 14% Li2O, 0 to 5% Na2O, 0 to 2% K2O, 0.5 to 12% in total of one or more of SnO2 and ZrO2, and 0 to 6% P2O5. Furthermore, when the crystal phase contains lithium silicate crystals, it preferably contains, in mass % on an oxide basis, 45 to 75% SiO2, 1 to 20% Al2O3, 10 to 25% Li2O, 0 to 10% Na2O, 0 to 5% K2O, 0 to 15% ZrO2, and 0 to 12% P2O5.

[0052] Each component will be described below. SiO2 is a component that forms the network structure of glass. It is also a component that increases chemical durability and is a component of the crystalline phase. The Si atoms that constitute SiO2 have a high first ionization energy of 8.2 eV and are easily reduced. The content of SiO2 is preferably 45% or more, more preferably 50% or more, and even more preferably 55% or more. In particular, when it is desired to increase the strength, the content of SiO2 is more preferably 58% or more, even more preferably 60% or more, and even more preferably 64% or more. On the other hand, from the viewpoint of obtaining good melting properties, the content of SiO2 is preferably 75% or less, more preferably 74% or less, even more preferably 70% or less, even more preferably 68% or less, and even more preferably 66% or less.

[0053] Al2O3 is an effective component for increasing the surface compressive stress by chemical strengthening. It also becomes a component of the crystal phase. The Al atoms constituting Al2O3 have a low first ionization energy of 6.0 eV, suppressing excessive reduction. The content of Al2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 5% or more, and even more preferably 8% or more. When it is desired to precipitate β-spodumene crystals, the content of Al2O3 is more preferably 15% or more, and even more preferably 20% or more. On the other hand, from the viewpoint of suppressing the increase in the devitrification temperature of the crystallized glass, the content of Al2O3 is preferably 30% or less, and more preferably 25% or less. In order to lower the forming temperature, the content of Al2O3 is more preferably 20% or less, and even more preferably 15% or less.

[0054] Li2O is a component that forms surface compressive stress by ion exchange, and is also a component of the crystal phase. The Li atoms that make up Li2O have a low first ionization energy of 5.4 eV, which suppresses excessive reduction. The content of Li2O is preferably 1% or more, more preferably 2% or more, and even more preferably 4% or more. In order to increase the amount of lithium metasilicate crystals precipitated as a crystalline phase, the Li2O content is preferably 10% or more, more preferably 15% or more, and particularly preferably 20% or more. In this case, the Li2O content is preferably 25% or less, more preferably 22% or less, and even more preferably 20% or less. When lithium aluminosilicate crystals are precipitated as the crystal phase, the Li2O content is preferably 14% or less, and when β-spodumene crystals are precipitated, the Li2O content is preferably 10% or less, more preferably 8% or less, and further preferably 6% or less.

[0055] When β-spodumene crystals are contained as the crystal phase, the content ratio of Li2O to Al2O3 expressed as Li2O / Al2O3 is preferably 0.3 or less, since this increases transparency.

[0056] Na2O is a component that improves the melting property of glass. The Na atom that constitutes Na2O has a low first ionization energy of 5.2 eV, which suppresses excessive reduction. Na2O may not be contained, but when it is contained, the content of Na2O is preferably 0.5% or more, more preferably 1% or more. On the other hand, from the viewpoint of easily precipitating a crystal phase and obtaining good chemical strengthening properties, the content of Na2O is preferably 15% or less, more preferably 12% or less, and even more preferably 10% or less. In order to precipitate β-spodumene crystals as a crystal phase, the content of Na2O is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less.

[0057] K2O is a component that lowers the melting temperature of glass like Na2O, and may be contained. When K2O is contained, the content is preferably 0.5% or more, more preferably 1% or more. From the viewpoint of lowering the forming temperature, the content of K2O is more preferably 1.5% or more, and further preferably 2% or more. Moreover, the total content of Na2O and K2O represented by Na2O+K2O is preferably 1% or more, and more preferably 2% or more.

[0058] On the other hand, from the viewpoint of obtaining good chemical strengthening properties, the content of K2O is preferably 8% or less, more preferably 7% or less, further preferably 6% or less, and particularly preferably 5% or less. From the viewpoint of easily precipitating lithium aluminosilicate crystals as a crystalline phase, the content of K2O is preferably 2% or less. In this case, the total content of Na2O and K2O expressed as Na2O+K2O is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less, from the viewpoint of preventing a decrease in transparency during heat treatment and increasing transparency. From the viewpoint of precipitating lithium metasilicate crystals as a crystalline phase while also obtaining good chemical strengthening properties, the content of K2O is preferably 4% or less, more preferably 3% or less, and particularly preferably 2% or less.

[0059] Although neither ZrO2 nor SnO2 is essential, they are components that form crystal nuclei during crystallization treatment, and it is preferable to contain at least one of them. The total content of SnO2 and ZrO2 expressed as SnO2+ZrO2 is preferably 0.5% or more from the viewpoint of crystal nucleation, and more preferably 1% or more. From the viewpoint of forming a large number of crystal nuclei to increase transparency, the total content is preferably 3% or more, more preferably 4% or more, even more preferably 5% or more, particularly preferably 6% or more, and most preferably 7% or more. On the other hand, from the viewpoint of suppressing devitrification during glass melting, the total content of SnO2 and ZrO2 is preferably 15% or less, and more preferably 14% or less. From the viewpoint of preventing defects due to unmelted matter from occurring in the glass, the total content is preferably 12% or less, more preferably 10% or less, even more preferably 9% or less, and particularly preferably 8% or less.

[0060] In order to facilitate the precipitation of lithium metasilicate crystals as a crystalline phase, it is preferable to contain ZrO2. In this case, the ZrO2 content is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, particularly preferably 6% or more, and most preferably 7% or more. In addition, in order to suppress devitrification during melting, the ZrO2 content is preferably 15% or less, more preferably 14% or less, even more preferably 12% or less, and particularly preferably 11% or less.

[0061] In order to facilitate the precipitation of β-spodumene crystals as a crystal phase, it is preferable to contain SnO2. In this case, the content of SnO2 is preferably 0.5% or more, more preferably 1% or more, and even more preferably 1.5% or more. In addition, in order to prevent defects due to unmelted matter from occurring in the crystallized glass, the content of SnO2 is preferably 6% or less, more preferably 5% or less, and even more preferably 4% or less.

[0062] In order to facilitate precipitation of β-spodumene crystals as a crystal phase, it is preferable to contain ZrO2. In this case, the content of ZrO2 is preferably 0.5% or more, more preferably 1% or more. In addition, in order to prevent devitrification during melting and maintain the quality of the crystallized glass obtained, the content of ZrO2 is preferably 6% or less, more preferably 5% or less, and even more preferably 4% or less.

[0063] In the case where β-spodumene crystals are to be precipitated as a crystalline phase, when both SnO2 and ZrO2 are contained, the ratio of the content of SnO2 to the total content of SnO2 and ZrO2, expressed as SnO2 / (SnO2+ZrO2), is preferably 0.3 or more, more preferably 0.35 or more, and even more preferably 0.45 or more, from the viewpoint of increasing transparency. Moreover, from the viewpoint of increasing strength, this ratio is preferably 0.7 or less, more preferably 0.65 or less, and even more preferably 0.60 or less.

[0064] SnO2 is also a component that enhances solarization resistance. From the viewpoint of suppressing solarization, the content of SnO2 is preferably 1% or more, and more preferably 1.5% or more.

[0065] TiO2 is a crystal nucleus forming component for glass-ceramics. From the viewpoint of facilitating precipitation of β-spodumene crystals as a crystal phase, the content of TiO2 when contained is preferably 0.1% or more, more preferably 0.15% or more, and even more preferably 0.2% or more. On the other hand, from the viewpoint of preventing devitrification during melting and maintaining the quality of the crystallized glass obtained, the content of TiO2 is preferably 5% or less, more preferably 3% or less, and even more preferably 1.5% or less. From the viewpoint of facilitating the precipitation of lithium metasilicate crystals as a crystalline phase, the content of TiO2 when it is contained is preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and most preferably 4% or more. On the other hand, from the viewpoint of preventing devitrification during melting and maintaining the quality of the crystallized glass obtained, the content of TiO2 is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less.

[0066] In addition, Fe2O3 is a component that may be normally contained as an impurity in crystallized glass. When Fe2O3 is contained, if the crystallized glass contains TiO2, a complex called an ilmenite complex is formed, which is likely to cause yellow or brown coloring. From the viewpoint of preventing such coloring, the content of TiO2 is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.25% or less, and it is particularly preferable that it is substantially not contained.

[0067] P2O5 is not essential, but may be contained since it has the effect of promoting phase separation of glass and accelerating crystallization. The P atom constituting P2O5 has a high first ionization energy of 10.5 eV and is easily reduced. When P2O5 is contained, the content is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, and particularly preferably 2% or more. From the viewpoint of facilitating precipitation of lithium metasilicate crystals as a crystalline phase, the content of P2O5 is more preferably 4% or more, even more preferably 5% or more, and particularly preferably 6% or more. On the other hand, from the viewpoint of maintaining good acid resistance, the content of P2O5 is preferably 15% or less, more preferably 14% or less, even more preferably 12% or less, even more preferably 11% or less, even more preferably 10% or less, particularly preferably 8% or less, and most preferably 7% or less. In the case where the crystal phase contains β-spodumene crystals, the content of P2O5 is preferably 6% or less, more preferably 5% or less, even more preferably 4% or less, particularly preferably 3% or less, and most preferably 2% or less, from the viewpoint of preventing fragments from scattering when the crystallized glass is broken. In addition, in the case where acid resistance is important, it is preferable that the glass does not substantially contain P2O5.

[0068] B2O3 is a component that improves chipping resistance and melting property, and may be contained. When B2O3 is contained, the content is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more from the viewpoint of improving melting property. On the other hand, from the viewpoint of suppressing the occurrence of striae during melting and maintaining the quality of the obtained crystallized glass, the content of B2O3 is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, and particularly preferably 1% or less. In addition, when importance is attached to acid resistance, it is preferable that B2O3 is not substantially contained.

[0069] MgO is a component that increases the surface compressive stress value of crystallized glass, and may be contained to suppress scattering of fragments when crystallized glass is broken. When MgO is contained, the content is preferably 0.5% or more, more preferably 1% or more. On the other hand, from the viewpoint of suppressing devitrification during melting, the content of MgO is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less.

[0070] CaO is a component that improves the meltability of glass, and may be contained to prevent devitrification during melting and improve the meltability while suppressing an increase in the thermal expansion coefficient. When CaO is contained, the content is preferably 0.5% or more, more preferably 1% or more. On the other hand, from the viewpoint of improving ion exchange properties, the content of CaO is preferably 4% or less, more preferably 3% or less, and particularly preferably 2% or less.

[0071] SrO is a component that improves the melting property of glass, and also improves the refractive index of glass, and brings the refractive index of the glass phase and the crystal phase after crystallization closer to each other, thereby improving the light transmittance of crystallized glass. When SrO is contained, the content is preferably 0.1% or more, more preferably 0.5% or more, and even more preferably 1% or more. On the other hand, in order to prevent the ion exchange rate from decreasing too much, the content of SrO is preferably 3% or less, more preferably 2.5% or less, even more preferably 2% or less, and particularly preferably 1% or less.

[0072] BaO is a component that improves the melting property of glass, and also improves the refractive index of glass, and brings the refractive index of the glass phase and the crystal phase close to each other after crystallization, thereby improving the light transmittance of crystallized glass. When BaO is contained, the content is preferably 0.1% or more, more preferably 0.5% or more, and even more preferably 1% or more. On the other hand, in order to prevent the ion exchange rate from decreasing too much, the content of BaO is preferably 3% or less, more preferably 2.5% or less, even more preferably 2% or less, and particularly preferably 1% or less.

[0073] ZnO is a component that reduces the thermal expansion coefficient of crystallized glass and increases chemical durability. It is also a component that improves the refractive index of glass and brings the refractive index of the glass phase and the crystal phase after crystallization closer to each other, thereby improving the light transmittance of crystallized glass. When ZnO is contained, the content is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, from the viewpoint of suppressing devitrification during melting, the content of ZnO is preferably 4% or less, more preferably 3% or less, and even more preferably 2% or less.

[0074] Y2O3, La2O3, Nb2O5 and Ta2O5 are all components that have the effect of suppressing scattering of fragments when the crystallized glass is broken, and increase the refractive index. When these components are contained, the total content of Y2O3, La2O3 and Nb2O5 represented by Y2O3+La2O3+Nb2O5 is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. In addition, from the viewpoint of suppressing devitrification of the glass during melting, the total content is preferably 4% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less.

[0075] The total content of Y2O3, La2O3, Nb2O5 and Ta2O5 represented by Y2O3+La2O3+Nb2O5+Ta2O5 is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. From the viewpoint of suppressing devitrification of the glass during melting, the total content is preferably 4% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less.

[0076] CeO2 has the effect of oxidizing glass, and when SnO2 is contained in a large amount, it may suppress coloring by suppressing the reduction of SnO2 to SnO, a coloring component. When CeO2 is contained, the content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.07% or more. On the other hand, from the viewpoint of preventing coloring of the crystallized glass and obtaining high transparency, the content of CeO2 is preferably 1.5% or less, and more preferably 1.0% or less.

[0077] In addition to the above, coloring components may be added within a range that does not impede the expression of the desired effects. Examples of coloring components include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, and Nd2O3. The total content of coloring components is preferably 1% or less, and in the case where it is desired to increase the light transmittance of the crystallized glass, it is preferable that these components are substantially not contained.

[0078] As a fining agent when melting glass, SO3, chloride, fluoride, etc. may be appropriately contained. It is preferable that As2O3 is not substantially contained. When Sb2O3 is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably substantially not contained.

[0079] <Method of manufacturing chemically strengthened glass-ceramics> The method for producing chemically strengthened crystallized glass according to this embodiment involves the following steps (a) to (d) in this order. Step (a): preparing an amorphous glass; Step (b): subjecting the amorphous glass of step (a) to a first heat treatment to obtain crystallized glass containing a crystalline phase; Step (c): A step of subjecting the crystallized glass obtained in step (b) to a second heat treatment in a reducing atmosphere to obtain crystallized glass having an amorphous region formed in a surface layer of at least one of the main surfaces; Step (d): A step of chemically strengthening the crystallized glass having the amorphous regions formed therein obtained in step (c).

[0080] Each step will be described in order. (Step (a)) The amorphous glass can be produced by a conventionally known method. For example, when obtaining a plate-shaped amorphous glass, it can be produced by the following method. Glass raw materials are mixed so as to obtain an amorphous glass of a desired composition, and are heated and melted in a glass melting furnace. The molten glass is then homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a known forming method, and slowly cooled. After homogenization, the molten glass may be formed into a block shape, slowly cooled, and then cut into a plate shape.

[0081] Examples of forming methods for plate glass include the float method, the press method, the fusion method, and the down-draw method. In particular, when producing a large glass plate, the float method is preferred. In addition, continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also preferred.

[0082] The glass composition of the amorphous glass can be, for example, the composition described in (Glass composition) of the above <Chemically strengthened crystallized glass>, and the preferred embodiments are also the same. It is also preferable to select the glass composition of the amorphous glass so that the crystallized glass obtained in the subsequent step (b) contains a desired crystalline phase.

[0083] The glass transition temperature Tg of the amorphous glass is not particularly limited, but from the viewpoint of facilitating structural relaxation during chemical strengthening treatment, it is preferably 600° C. or less, more preferably 580° C. or less, and even more preferably 550° C. or less. In addition, since the melting point of sodium nitrate is around 380° C., the glass transition temperature Tg is preferably 450° C. or more.

[0084] (Step (b)) By subjecting the amorphous glass prepared in step (a) to a first heat treatment, crystallized glass containing a crystalline phase is obtained. The first heat treatment is not particularly limited as long as a crystal phase is formed, but from the viewpoint of generating a large number of crystal nuclei and achieving good crystal growth, it is preferable to carry out two or more stages of heat treatment.

[0085] When performing a two-stage heat treatment, it is preferable to, for example, raise the temperature from room temperature to a first-stage heat treatment temperature and hold it for a certain period of time, and then hold it for a certain period of time at a second-stage heat treatment temperature that is higher than the first-stage heat treatment temperature. When a three-stage heat treatment is performed, for example, in addition to the above two heat treatment stages, it is preferable to further hold the third heat treatment temperature, which is higher than the second heat treatment temperature, for a certain period of time.

[0086] In the case of a two-stage heat treatment, the first stage heat treatment temperature is preferably in a temperature range in which the crystal nucleation rate is high for that glass composition, and the second stage heat treatment temperature is preferably in a temperature range in which the crystal growth rate is high for that glass composition.

[0087] It is preferable to hold the first heat treatment temperature for a long time so that a sufficient number of crystal nuclei are generated. By generating a large number of crystal nuclei, the size of each crystal becomes small, and a highly transparent crystallized glass is obtained.

[0088] The first stage heat treatment temperature in the first heat treatment is, for example, 550° C. or more and 800° C. or less. The second stage heat treatment temperature in the first heat treatment is, for example, 850° C. or more and 1000° C. or less. The first stage heat treatment temperature is maintained for, for example, 2 to 10 hours, and then the second stage heat treatment temperature is maintained for, for example, 2 to 10 hours.

[0089] The first heat treatment makes the crystallinity of the resulting crystallized glass exceed 15% by volume. From the viewpoint of realizing a more desired stress profile by relaxing the structure due to the heat during the chemical strengthening treatment in step (d), the crystallinity of the crystallized glass is preferably 20% by volume or more, more preferably 25% by volume or more, and even more preferably 30% by volume or more. On the other hand, from the viewpoint of maintaining the transparency of the crystallized glass, the crystallinity is preferably 90% by volume or less, and more preferably 80% by volume or less.

[0090] The average crystallinity of the crystallized glass can be adjusted to a desired value by adjusting the temperature and time of the first heat treatment. Even if the subsequent step (c) of forming an amorphous region on the surface of the crystallized glass is performed, the average crystallinity of the inside of the crystallized glass does not change. The same is true even if a chemical strengthening treatment is performed in step (d). Therefore, the average crystallinity of the glass-ceramics realized in the step (b) is equal to the average crystallinity of the chemically strengthened glass-ceramics.

[0091] (Process (c)) The crystallized glass obtained in the step (b) is subjected to a second heat treatment in a reducing atmosphere to obtain crystallized glass having an amorphous region formed in the surface layer of at least one of its main surfaces.

[0092] The second heat treatment is not particularly limited as long as it is performed in a reducing atmosphere. For example, heat treatment in a reducing gas atmosphere or heat treatment in contact with carbon is preferable, and heat treatment in contact with carbon is more preferable.

[0093] Reducing gases include hydrogen (H2) gas, carbon monoxide (CO) gas, and hydrocarbon gas (C n H 2n+1 ) is preferred.

[0094] When the heat treatment is performed in a reducing gas atmosphere, a mixed gas in which the reducing gas is mixed with other gases may be used, such as nitrogen (N2) gas, argon gas, etc. When N2+H2 gas is used as the mixed gas, the H2 gas content is preferably 1% by volume or more in order to obtain sufficient reducing properties, and is preferably 4% by volume or less in order to suppress the risk of explosion.

[0095] From the viewpoint of obtaining sufficient reducing ability, the heat treatment temperature T2 (°C) in the second heat treatment is preferably higher than (Tg-200)°C, more preferably higher than (Tg-150)°C, and even more preferably higher than (Tg-120)°C, with respect to the glass transition temperature Tg (°C) of the amorphous glass. Also, from the viewpoint of suppressing crystal growth, the heat treatment temperature T2 (°C) is preferably lower than (Tg+200)°C, more preferably lower than (Tg+150)°C, and even more preferably lower than (Tg+100)°C.

[0096] By carrying out the second heat treatment in a reducing atmosphere, an amorphous region is formed on the surface of the crystallized glass. Although the details of this are unclear, it is speculated that this is because some of the atoms that make up the crystalline phase are reduced and are no longer able to maintain their crystalline state.

[0097] The amorphous region may be formed on at least one of the main surfaces of the crystallized glass, but is preferably formed on both main surfaces from the viewpoint of improving strength. Moreover, the amorphous region may be formed not only on the main surfaces but also on the end surfaces.

[0098] The depth of the amorphous region from the outermost surface is preferably 10 μm or less, but the depth of the amorphous region can be adjusted by changing the temperature and reducing power of the second heat treatment.

[0099] The degree of crystallinity at a depth of 100 nm from the outermost surface of the amorphous region is preferably 10% by volume or less. It is also possible for the degree of crystallinity at the outermost surface of the amorphous region to be 0% by volume, i.e., the entire surface may be a glass phase. The degree of crystallinity in such an amorphous region and the profile of the degree of crystallinity in the depth direction can be adjusted by controlling the temperature and atmosphere when the crystallized glass is heat-treated in a reducing atmosphere.

[0100] When the chemically strengthened crystallized glass is used for a three-dimensional shape such as a cover glass, it is preferable to mold the crystallized glass into a shape having a curved portion simultaneously with the second heat treatment.

[0101] The bending method for forming a shape having a curved portion can be selected from existing bending methods such as gravity forming, vacuum forming, press forming, etc. Two or more bending methods may be used in combination.

[0102] The gravity forming method is a method in which a crystallized glass plate is placed on a mold, heated, and conformed to the mold by gravity, and bent into a predetermined shape. The vacuum forming method is a method in which a crystallized glass plate is placed on a forming mold, the periphery of the crystallized glass plate is sealed, and then the space between the forming mold and the crystallized glass plate is depressurized, and a pressure difference is applied between the front and back sides of the crystallized glass plate to bend the crystallized glass plate. At this time, the upper side of the crystallized glass plate may be additionally pressurized. Press molding is a method in which a crystallized glass plate is placed between a lower mold and an upper mold, the crystallized glass plate is heated, and a press load is applied between the upper and lower molds to bend the plate into a predetermined shape. All of the bending methods described above are methods in which crystallized glass is deformed by applying force while it is heated. It is also preferable to use a carbon molding die during molding. This is because a reducing atmosphere is created by contacting the carbon with the glass plate, and molding can be performed while obtaining the reducing atmosphere in step (c). When a carbon molding die is used, it is preferable that the mold is pressed against both main surfaces of the crystallized glass from the outside, as both main surfaces are uniformly made amorphous, and thus the glass does not warp during chemical strengthening treatment.

[0103] The bending (hot bending) temperature is, for example, 700°C to 1100°C, preferably 750°C or higher, and preferably 1050°C or lower. If the heat bending temperature is higher than the maximum temperature of the heat treatment in the crystallization treatment, i.e., step (b), thermal deformation easily occurs, which is preferable from the viewpoint of dimensional accuracy. The difference between the maximum temperature of the crystallization treatment and the heat bending temperature is preferably 10°C or higher, more preferably 30°C or higher. On the other hand, from the viewpoint of preventing a decrease in light transmittance due to bending, the difference between the maximum temperature of the crystallization treatment and the heat bending temperature is preferably 120°C or lower, more preferably 100°C or lower, even more preferably 90°C or lower, and particularly preferably 60°C or lower.

[0104] The decrease in light transmittance due to bending is preferably 3% or less, more preferably 2% or less, further preferably 1.5% or less, and particularly preferably 1% or less. In order to maintain high transparency of the final crystallized glass, it is advantageous to have a high light transmittance before heat bending, and the light transmittance converted into a thickness of 0.7 mm is preferably 85% or more, more preferably 87% or more, and particularly preferably 89% or more.

[0105] (Step (d)) The glass-ceramics having the amorphous regions formed therein obtained in the step (c) is subjected to a chemical strengthening treatment to obtain a chemically strengthened glass-ceramics.

[0106] Chemical strengthening is a process in which the crystallized glass in which the amorphous regions have been formed is immersed in a molten solution of a metal salt containing metal ions with a large ionic radius, and the metal ions with a small ionic radius in the crystallized glass are replaced with metal ions with a large ionic radius. Typically, Li ions are replaced with Na ions or K ions, and Na ions are replaced with K ions.

[0107] In order to increase the speed of chemical strengthening, it is preferable to use "Li-Na exchange" in which Li ions in the crystallized glass are exchanged with Na ions. Also, in order to create a large compressive stress by ion exchange, it is preferable to use "Na-K exchange" in which Na ions in the crystallized glass are exchanged with K ions.

[0108] Examples of molten salts for performing chemical strengthening treatment include nitrates, sulfates, carbonates, and chlorides. Among these, examples of nitrates include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, and silver nitrate. Examples of sulfates include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, and silver sulfate. Examples of carbonates include lithium carbonate, sodium carbonate, and potassium carbonate. Examples of chlorides include lithium chloride, sodium chloride, potassium chloride, cesium chloride, and silver chloride. These molten salts may be used alone or in combination.

[0109] The treatment conditions, such as the time and temperature, of the chemical strengthening treatment may be appropriately selected in consideration of the glass composition, the type of molten salt, and the like.

[0110] The chemically strengthened glass-ceramics may be obtained, for example, by the following two-stage chemical strengthening treatment. As the first stage of chemical strengthening treatment, the crystallized glass having an amorphous region formed on the surface is immersed in a metal salt containing Na ions, such as sodium nitrate molten salt, at about 350 to 500 ° C. for about 0.1 to 10 hours. This causes ion exchange between the Li ions in the crystallized glass and the Na ions in the metal salt, forming a compressive stress layer with a surface compressive stress value of 200 MPa or more and a compressive stress layer depth of 80 μm or more. If the surface compressive stress value introduced in the first stage treatment exceeds 1000 MPa, it may be difficult to increase the compressive stress layer depth (DOL) while keeping the internal stress (CT) low in the finally obtained chemically strengthened crystallized glass. Therefore, the surface compressive stress value introduced in the first stage treatment is preferably 900 MPa or less, more preferably 700 MPa or less, and even more preferably 600 MPa or less.

[0111] As the second stage of chemical strengthening treatment, the above-mentioned crystallized glass that has been subjected to the first stage of treatment is immersed for about 0.1 to 10 hours in a metal salt containing K ions, such as potassium nitrate molten salt, at about 350 to 500° C. As a result, a large compressive stress is generated in a portion of the compressive stress layer formed in the previous treatment, for example, at a depth of about 10 μm or less.

[0112] Such a two-stage chemical strengthening treatment makes it easy to obtain a favorable stress profile with a surface compressive stress value of 600 MPa or more.

[0113] The two-stage chemical strengthening treatment may be performed by first immersing the material in a metal salt containing Na ions, then holding the material in air at 350 to 500° C. for 1 to 5 hours, and then immersing the material in a metal salt containing K ions. The holding temperature in the atmosphere is preferably 425° C. or higher, more preferably 440° C. or higher, and is preferably 475° C. or lower, more preferably 460° C. or lower. By holding at a high temperature in the atmosphere, the Na ions introduced from the metal salt into the crystallized glass by the first-stage treatment are thermally diffused in the crystallized glass, forming a more preferable stress profile.

[0114] After immersing in the metal salt containing Na ions in the first stage of treatment, instead of holding in the air, the crystallized glass may be immersed in a metal salt containing Na ions and Li ions, such as a mixed molten salt of sodium nitrate and lithium nitrate, at 350 to 500°C for 0.1 to 20 hours. By immersing the glass in a metal salt containing Na and Li ions, ion exchange occurs between the Na ions in the crystallized glass and the Li ions in the metal salt, forming a more favorable stress profile and thereby increasing the drop strength. This corresponds to a three-stage chemical strengthening process.

[0115] When performing such a two- or three-stage chemical strengthening treatment, the total treatment time is preferably 10 hours or less, more preferably 5 hours or less, and even more preferably 3 hours or less, from the viewpoint of production efficiency. On the other hand, in order to obtain a desired stress profile, the total treatment time is preferably 0.5 hours or more, and more preferably 1 hour or more.

[0116] The chemically strengthened crystallized glass according to the present embodiment obtained as described above may have a shape other than a plate shape depending on the product or use to which it is applied. The chemically strengthened crystallized glass may have a border shape with different thicknesses on the periphery. The form of the chemically strengthened crystallized glass is not limited to this, and for example, the two main surfaces may not be parallel to each other, and one or both of the two main surfaces may be entirely or partially curved. More specifically, the chemically strengthened crystallized glass may be, for example, a flat glass plate without warping, or a curved glass plate having a curved surface.

[0117] Chemically strengthened crystallized glass is particularly useful as a cover glass for mobile devices such as mobile phones and smartphones. It is also useful as a cover glass for display devices such as televisions, personal computers, and touch panels that are not intended to be portable. It is also useful for elevator walls and walls of buildings such as houses and buildings, i.e., full-surface displays. In addition to the above, it is also useful as building materials such as window glass, table tops, interiors of automobiles and airplanes, and cover glasses for these, and for applications such as curved housings. EXAMPLES

[0118] The present invention will be described below with reference to examples, but the present invention is not limited thereto. Examples 1 to 3 are working examples, and Examples 4 and 5 are comparative examples.

[0119] (Example 1) Glass raw materials were prepared and mixed to obtain the glass composition shown in mass % based on oxides in Glass A in Table 1. Next, the mixed glass raw materials were placed in a platinum crucible and put into an electric furnace at 1600°C to melt for about 4 hours, degassed, and homogenized. The obtained molten glass was poured into a mold and held at a temperature about 30°C higher than the glass transition point, i.e., 500°C, for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block was processed into a plate of about 60 mm x 60 mm x 0.7 mm to obtain an amorphous glass having two main surfaces facing each other. Next, the amorphous glass was subjected to a first heat treatment in which it was held at 550° C. for 2 hours and then held at 730° C. for 2 hours to perform a crystallization treatment, thereby obtaining glass A, which was crystallized glass. Next, as a second heat treatment, heat treatment was performed at 690° C. for 3 minutes in a 98 vol % N 2 -2 vol % H 2 gas atmosphere to form an amorphous region in the surface layer of the main surface. Thereafter, the glass was immersed in a molten sodium nitrate at 450° C. for 2.4 hours to perform a chemical strengthening treatment, thereby obtaining a chemically strengthened crystallized glass. In addition, the blank spaces in the glass compositions shown in Table 1 mean that the content of the corresponding component is below the detection limit.

[0120] (Example 2) In the second heat treatment, a carbon mold was pressed against both main surfaces of the glass from the outside to bring them into contact with each other, creating a reducing atmosphere. In this state, heat treatment was performed at 690°C for 3 minutes to form amorphous regions on the surface layers of both main surfaces, and chemically strengthened crystallized glass was obtained in the same manner as in Example 2. By using the carbon mold, the edges of the obtained glass were processed into a three-dimensional shape with curved portions.

[0121] (Example 3) Glass raw materials were prepared and mixed to obtain the glass composition shown in mole percent based on oxides in Glass B in Table 1. The mixed glass raw materials were then placed in a platinum crucible and placed in an electric furnace at 1600°C to melt for about 4 hours, degassed, and homogenized. The obtained molten glass was poured into a mold and held at a temperature about 30°C higher than the glass transition point, i.e., 745°C, for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block was processed into a plate of about 60 mm x 60 mm x 0.7 mm to obtain an amorphous glass having two main surfaces facing each other. Next, the amorphous glass was subjected to a first heat treatment in which it was held at 750° C. for 4 hours and then held at 900° C. for 4 hours for crystallization, thereby obtaining glass B, which was crystallized glass. Next, as the second heat treatment, a carbon mold was pressed against both main surfaces of the glass from the outside to bring them into contact with each other, creating a reducing atmosphere. In this state, heat treatment was performed at 787°C for 6 minutes to form amorphous regions on the surface layers of both main surfaces. By using the carbon mold, the edges of the obtained glass were processed into a three-dimensional shape with curved parts. The glass was then immersed in a sodium nitrate molten salt at 450°C for 0.5 hour, and then in a potassium nitrate molten salt at 450°C for 1 hour, performing a two-stage chemical strengthening treatment to obtain chemically strengthened crystallized glass.

[0122] (Example 4) A chemically strengthened crystallized glass was obtained in the same manner as in Example 1, except that the second heat treatment was carried out in air.

[0123] (Example 5) A chemically strengthened crystallized glass was obtained in the same manner as in Example 3, except that the second heat treatment was carried out in the atmosphere without contacting a carbon molding die.

[0124] <Evaluation method> (Glass transition temperature Tg(℃)) For the amorphous glass and the crystallized glass after the first heat treatment, thermal expansion curves were obtained using a thermal dilatometer (manufactured by Bruker AXS; TD5000SA) at a heating rate of 10°C / min according to JIS R1618:2002. The glass transition temperature Tg (°C) was calculated from the obtained thermal expansion curves. The results are shown in Table 1.

[0125] (Crystallization rate (volume%)) The crystallinity of the glass was calculated from a TEM image obtained by observation with a transmission electron microscope (EM-2010F, TEM, manufactured by JEOL Ltd.). As examples of TEM images, in Example 3, a TEM image of the amorphous glass before the first heat treatment is shown in FIG. 1, a TEM image of the crystallized glass obtained after the first heat treatment is shown in FIG. 2, and a TEM image of the crystallized glass obtained after the second heat treatment is shown in FIG. 3. In Figure 1, the region with a uniform structure that occupies the majority of the image is glass. The light-colored region located on the surface of the glass and the black region located on the surface of the light-colored region are, respectively, a carbon coating layer formed by carbon deposition and a Pt coating layer formed by platinum sputtering, which were performed during TEM observation. It was confirmed that the glass in Figure 1 has a uniform structure with no clear boundaries between light and dark areas, and that there is no crystalline phase, only a glass phase, i.e., an amorphous phase. On the other hand, in Figure 2, the majority of the region is glass, but unlike Figure 1, dark dots and granular regions with clear boundaries are observed. These dark dots are crystal nuclei, and the granular regions with clear boundaries are the crystalline phase. Considering the difference between these two figures, in Fig. 3 showing the crystallized glass obtained after the second heat treatment in Example 3, there is no clear boundary between light and dark from the surface layer of the glass in contact with the black region, which is the Pt coating layer, to a certain depth. Therefore, it can be seen that there is no crystalline phase or only a slight crystalline phase in the surface layer of the main surface of the glass, and an amorphous region is formed.

[0126] For the chemically strengthened crystallized glass, the crystallinity at each target depth was calculated for depths of 100 nm to 500 nm from the outermost surface, and for depths of 500 nm and beyond, any depth was set as the target depth. Specifically, in a TEM image of the target depth, the total length X μm of the crystalline phase present within a range of 1 μm in a direction parallel to any main surface and 0.05 μm in the depth direction was measured, and the value represented by (X / 0.05) was taken as the crystallinity (volume %). As an example, the relationship between the crystallinity and the depth from the outermost surface of the chemically strengthened crystallized glass of Example 2 and Example 3 is shown in Figures 4 and 6, respectively.

[0127] The value at which the degree of crystallinity becomes constant in the depth direction is the average degree of crystallinity of the crystallized region of the chemically strengthened crystallized glass having an amorphous region formed on the surface layer, and is the same value as the degree of crystallization of the crystallized glass before the amorphous region is formed. The depth at which the crystallinity was 10% by volume was defined as the depth of the amorphous region for the chemically strengthened glass-ceramics. The results are shown in Table 2 together with the crystallinity at a depth of 100 nm from the outermost surface.

[0128] (Sodium concentration (mol%)) For the chemically strengthened glass-ceramics of Examples 1 to 5, the sodium concentration [Na] in a region at a depth of 230 μm or more from the outermost surface was measured by an electron probe microanalyzer (JXA-8500F, EPMA, manufactured by JEOL Ltd.). For the chemically strengthened crystallized glass of Example 2, the sodium concentration [Na]0 at a depth of 10 nm from the outermost surface was measured using an X-ray photoelectron spectrometer (ULVAC-PHI, Inc.; ESCA5500, XPS). The measurement conditions for XPS were as follows: Detection area: 800 μmφ, Detection angle: 75 deg to the sample surface, Pass Energy: 117.4 eV, Energy Step: 0.5 eV / step, Sputter ion species: C 60 + , Sputtering setting: Voltage 10kV, Raster size: 3×3.5mm 2 Measurement interval: 2 minutes As an example, the relationship between the sodium concentration and the depth from the outermost surface of the chemically strengthened crystallized glasses of Examples 2 and 3 are shown in FIGS. 8 and 9, respectively. The sodium concentration at a depth of 10 nm from the outermost surface is calculated by fitting the sodium concentration profile in the region from 10 to 200 μm deep from the outermost surface to the following formula (1) using the least squares method, and is defined as [Na] c The results are shown in Table 2. For Example 2, the sodium concentration [Na]0 (mol%) at a depth of 10 nm from the outermost surface obtained from the results of XPS measurement, as well as |[Na]0-[Na] c The absolute value of the sodium concentration difference represented by | and [Na]0 and [Na] c The ratio is also shown in Table 2. y = A × erfc(x × B) + C (1) (In the formula, y is the sodium concentration (mol%), x is the depth from the main surface (μm), erfc is the complementary error function, A, B, and C are constants, and 0≦x≦200.) The constants in formula (1) in Example 1 were A = 6.712, B = 0.012, and C = 1.521. The constants in formula (1) in Example 2 were A = 6.799, B = 0.011, and C = 1.546. The constants in formula (1) in Example 3 were A = 6.844, B = 0.014, and C = 1.849. The constants in formula (1) in Example 4 were A = 6.521, B = 0.009, and C = 1.621. The constants in formula (1) in Example 5 were A = 6.831, B = 0.014, and C = 1.802.

[0129] (crystalline phase) The chemically strengthened glass-ceramics was subjected to powder X-ray diffraction (Rigaku Corporation; SmartLab, XRD) measurement to identify the crystal phase. The measurement conditions were: X-ray source: CuKα radiation, measurement range: 2θ = 10° to 80°, scan speed: 10° / min, step width: 0.02°. The results are shown in Table 2. The crystal phase of the chemically strengthened glass-ceramics can be considered to be the same as the crystal phase of the glass-ceramics. The first ionization energies of some of the elements that constitute the crystal phase are shown below. Li=5.4eV, Na=5.2eV, Al=6.0eV, Si=8.2eV

[0130] (Compressive stress value (CS)) The stress profile of the chemically strengthened crystallized glass at a depth of 10 μm or more from the outermost surface was measured using a surface stress meter (Orihara Seisakusho Co., Ltd.; FSM-6000) and a measuring device that applies scattered light photoelasticity (Orihara Seisakusho Co., Ltd.; SLP1000). The compressive stress values ​​at the outermost surface and at a depth less than 10 μm from the outermost surface were calculated by converting the radius of curvature of the warp caused by etching only one of a pair of opposing main surfaces, and then converting the radius of curvature into stress using the following formula shown in the following reference document. Specifically, one of the main surfaces was sealed and immersed in 1% HF-99% H2O (volume fraction) acid, and the other main surface was etched to an arbitrary thickness. This caused a stress difference between the front and back surfaces of the chemically strengthened crystallized glass, which warped in response to the stress difference. The amount of warping was measured using a contact shape meter (Mitutoyo; Surftest). CS0=Et 2 / 6(1-ν)Rt' (In the formula, E represents the Young's modulus of the glass, t represents the thickness of the glass, ν represents the Poisson's ratio of the glass, R represents the radius of curvature of the warp of the glass, and t' represents the thickness of the etched portion.) (Reference: GGStoney, Proc. Roy. Soc. A82, 172 (1909))

[0131] As examples obtained above, the stress profiles of the chemically strengthened glass-ceramics of Examples 2 and 3 are shown in Figs. 5 and 7, respectively. The compressive stress value CS0 at the outermost surface where the amorphous region is formed, the compressive stress value CS5 at a depth of 5 μm from the outermost surface, and the compressive stress value CS at a depth of 50 μm from the outermost surface, which are obtained from the stress profile, are 50 , and the maximum value of the compressive stress (CS max ) and C.S. max Table 2 shows the depth from the outermost surface at which this can be achieved.

[0132] (Sodium ion diffusion depth) The sodium ion diffusion depth of the chemically strengthened glass-ceramics was measured using an electron probe microanalyzer (JEOL; JXA-8500F, EPMA). Although it is difficult to accurately measure the sodium concentration at the outermost surface using EPMA, this does not have a significant effect on the measurement of the sodium ion diffusion depth, which corresponds to the depth of the compressive stress layer (DOL). The results are shown in Table 2.

[0133] (4-point bending strength) A four-point bending test was performed under the conditions of a distance between the outer supports of the fixture of 30 mm, a distance between the inner supports of 10 mm, and a crosshead speed of 0.5 mm / min, and the four-point bending strength was measured. Ten test pieces were used, and the average strength was taken as the four-point bending strength. The results are shown in Table 2.

[0134] (Drop strength) The chemically strengthened crystallized glass was cut into 120mm x 60mm x 0.7mm to be used as a test piece, which resembled the cover glass of a smartphone. This test piece was attached to a housing simulating a smartphone and dropped onto a flat surface with 180-grit sandpaper. The combined mass of the test piece and the housing was approximately 140g. The drop test was started from a height of 30cm, and if the glass plate, which was the test piece, did not break, the test was repeated by increasing the height by 10cm and the height at which it broke was recorded. This test was repeated 10 times, which was considered as one set, and the average value of the height at which it broke was taken as the drop strength. The results are shown in Table 2.

[0135] (Chipping probability) 100 pieces of each chemically strengthened glass-ceramic obtained through the chemical strengthening process were left to stand for 24 hours. After leaving them to stand, the probability of chipping was calculated from the number of samples in which chipping was found on the end face. The results are shown in Table 2.

[0136] [Table 1]

[0137] [Table 2]

[0138] From the above results, it was found that by subjecting the crystallized glass to the second heat treatment in a reducing atmosphere, an amorphous region was formed on the surface layer of the glass. The presence of this amorphous region provided excellent chemical strengthening characteristics for the subsequent chemical strengthening treatment, and the ion diffusion rate toward the inside of the glass was improved, resulting in improved internal compressive stress, such as 5 μm or 50 μm from the outermost surface. In addition, it was found that the compressive stress value of the outermost surface of the chemically strengthened crystallized glass according to this embodiment was smaller than that of crystallized glass not having an amorphous region, and the surface stress was relaxed. As a result, it was possible to realize excellent strength characteristics by chemical strengthening treatment for the crystallized glass, while suppressing chipping after the chemical strengthening treatment.

[0139] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2020-130798) filed on July 31, 2020, the contents of which are incorporated herein by reference.

Claims

1. A chemically strengthened crystallized glass containing a crystalline phase, having two main surfaces opposed to each other, The glass has an amorphous region on a surface layer of at least one of the main surfaces and a crystallized region inside the glass, The degree of crystallization of the amorphous region at a depth of 100 nm from the outermost surface is 10% by volume or less.

2. Contains sodium, The sodium concentration at a depth of 10 nm from the outermost surface is [Na] 0 (mol %), and the sodium concentration at a depth of 10 nm from the outermost surface calculated by fitting the sodium concentration profile in the region from the outermost surface to a depth of 10 to 200 μm to the following formula (1) by the least squares method is [Na] c When this is done, |[Na] 0 - [Na] c 2. The chemically strengthened crystallized glass according to claim 1, wherein the absolute value of the sodium concentration difference represented by | is 10 mol % or less. y=A×erfc(x×B)+C...(1) (In the formula, y is the sodium concentration (mol %), x is the depth from the main surface (μm), erfc is the complementary error function, A, B, and C are constants, and 0≦x≦200.)

3. 3. The chemically strengthened crystallized glass according to claim 1, wherein the average crystallinity of the crystallized regions is 20 to 80 volume %.

4. The chemically strengthened crystallized glass according to any one of claims 1 to 3, wherein the depth of the amorphous region is 10 µm or less.

5. The compressive stress value CS on the outermost surface 0 The chemically strengthened crystallized glass according to any one of claims 1 to 4, wherein the strain is 200 to 900 MPa.

6. The chemically strengthened crystallized glass according to any one of claims 1 to 5, wherein the depth from the outermost surface at which the compressive stress value CS is maximum is 0.1 to 10 µm.

7. The chemically strengthened crystallized glass according to any one of claims 2 to 6, wherein the sodium ion diffusion depth is (t x 0.05) to (t x 0.2) µm, where t µm is the thickness of the glass.

8. The chemically strengthened crystallized glass according to any one of claims 1 to 7, wherein the crystal phase contains atoms having a first ionization energy of 8 eV or less.

9. In terms of mass% based on oxides, SiO 2 45 to 75% Al 2 O 3 を1~30%、 Li 2 Oを1~25%、 Na 2 Oを0~15%、 K 2 O 0 to 8%, SnO 2 and ZrO 2 Any one or more of the following in total: 0 to 15%; and P 2 O 5 The chemically strengthened crystallized glass according to any one of claims 1 to 8, containing 0 to 15%.

10. Providing an amorphous glass; subjecting the amorphous glass to a first heat treatment to obtain crystallized glass containing a crystalline phase; subjecting the crystallized glass to a second heat treatment in a reducing atmosphere to obtain a crystallized glass having an amorphous region formed in a surface layer of at least one of the main surfaces; and Chemically strengthening the crystallized glass in which the amorphous region is formed; A method for producing chemically strengthened crystallized glass, comprising the steps of:

11. The amorphous region is formed in a region having a depth of 10 μm or less from the outermost surface, The method for producing chemically strengthened crystallized glass according to claim 10, wherein the degree of crystallization of the amorphous region at a depth of 100 nm from the outermost surface is 10% by volume or less.

12. 12. The method for producing chemically strengthened crystallized glass according to claim 10, wherein the average crystallinity of the crystallized glass obtained by the first heat treatment is 20 to 80 volume %.

13. The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 12, wherein the amorphous glass has a glass transition temperature Tg of 550°C or lower.

14. The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 13, wherein the heat treatment temperature T2 (°C) in the second heat treatment satisfies the relationship of (Tg-200)°C<T2<(Tg+200)°C with respect to the glass transition temperature Tg (°C) of the amorphous glass.

15. The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 14, wherein the second heat treatment is carried out in a state where the crystallized glass is in contact with carbon.

16. The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 15, wherein the glass is formed into a shape having a curved portion during the second heat treatment.

17. The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 16, wherein the crystal phase contains atoms having an ionization energy of 8 eV or less.

18. The amorphous glass has, in mass % on an oxide basis, SiO 2 45 to 75% Al 2 O 3 を1~30%、 Li 2 Oを1~25%、 Na 2 Oを0~15%、 K 2 O 0 to 8%, SnO 2 and ZrO 2 Any one or more of the following in total: 0 to 15%; and P 2 O 5 The method for producing chemically strengthened crystallized glass according to any one of claims 10 to 17, wherein the glass contains 0 to 15% of

Citation Information

Patent Citations

  • Crystallized glass article for construction material and production of the article

    JP1996225343A

  • Microlens and microlens array

    JP2005062832A

  • Method for producing crystallized glass plate

    JP2010070411A

  • A transparent glass-ceramic material containing lithium, having a low coefficient of thermal expansion, a substantially amorphous, lithium-deficient, primarily glassy surface region, and high transmittance, its manufacture and use in an aqueous atmosphere.

    JP2013533200A

  • High-strength glass-ceramics with lithium disilicate and β-spodumene structures

    JP2016529201A